2018
DOI: 10.1136/bmjgast-2018-000225
|View full text |Cite
|
Sign up to set email alerts
|

Discharge of patients with an acute upper gastrointestinal bleed from the emergency department using an extended Glasgow-Blatchford Score

Abstract: ObjectiveTo use an extended Glasgow-Blatchford Score (GBS) cut-off of ≤1 to aid discharge of patients presenting with acute upper gastrointestinal bleeding (AUGIB) from emergency departments.BackgroundThe GBS accurately predicts the need for intervention and death in AUGIB, and a cut-off of 0 is recommended to identify patients for discharge without endoscopy. However, this cut-off is limited by identifying a low percentage of low-risk patients. Extension of the cut-off to ≤1 or ≤2 has been proposed to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
0
21
2
Order By: Relevance
“…In our study, in predicting need for blood transfusion, all scores performed well, but modified AIMS65 had slightly better accuracy; however, in predicting need for endoscopic intervention, only modified AIMS65, GBS and FRS had meaningful accuracy (p < 0.05). Although, outperformance of GBS in assessment of need for clinical intervention has been shown in other studies [20,[24][25][26], we found modified AIMS65 as a good fit alternative.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…In our study, in predicting need for blood transfusion, all scores performed well, but modified AIMS65 had slightly better accuracy; however, in predicting need for endoscopic intervention, only modified AIMS65, GBS and FRS had meaningful accuracy (p < 0.05). Although, outperformance of GBS in assessment of need for clinical intervention has been shown in other studies [20,[24][25][26], we found modified AIMS65 as a good fit alternative.…”
Section: Discussioncontrasting
confidence: 57%
“…Increasing the cutoff point acts as two edged sword. Higher cut off can identify more low risk patient leading to even more reduction in cost; while, in the meantime, the risk of adverse outcome increases [2,14,24,38]. In our study no patients died within GBS ≤ 2 and 3.39% had adverse outcome of 30-day rebleeding and need for endoscopic therapy while in AIMS65 = 0, 14.28% had adverse outcome and 1.29 % (3 patients) had mortality.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations